1971
DOI: 10.1577/1548-8659(1971)100<290:fhlrac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits, Length-Weight Relationship, and Condition Factor of the Red Drum (Sciaenops ocellata) in Southeastern Louisiana

Abstract: A total of 349 adult red drum (Sciaenops ocellata) were collected from the coastal marsh below Hopedale in southeastern Louisiana, between October, 1967 and October, 1968. A total of 286 fish (82%) contained identifiable food items which were analyzed as to frequency of occurrence and percent of total volume. The main food items in order of occurrence were fish, shrimp, and crabs. Blue crabs, mud crabs, and penaeid shrimp were the crustaceans most frequently eaten, and at least 14 different species of fish wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In the western Gulf of Mexico adult red drum reside offshore for much of the year and migrate to coastal inlets for spawning in late summer. As a result of this migration, their diet shifts from approximately 55% fish and 38% crustaceans in winter and spring (offshore) to 28% fish and 65% crustaceans in late summer (inshore), principally replacing DHA-rich menhaden (Brevoortia patronus) with white shrimp [26,27] at the time when oocytes are being supplied with yolk. Thus despite containing somewhat less DHA, the shrimp (together with blue crab, Callinectes sapidus, which does not vary seasonally in the diet) represent an important source of DHA for red drum eggs.…”
Section: (B) Ecological Implications Of Metabolic Programmingmentioning
confidence: 99%
“…In the western Gulf of Mexico adult red drum reside offshore for much of the year and migrate to coastal inlets for spawning in late summer. As a result of this migration, their diet shifts from approximately 55% fish and 38% crustaceans in winter and spring (offshore) to 28% fish and 65% crustaceans in late summer (inshore), principally replacing DHA-rich menhaden (Brevoortia patronus) with white shrimp [26,27] at the time when oocytes are being supplied with yolk. Thus despite containing somewhat less DHA, the shrimp (together with blue crab, Callinectes sapidus, which does not vary seasonally in the diet) represent an important source of DHA for red drum eggs.…”
Section: (B) Ecological Implications Of Metabolic Programmingmentioning
confidence: 99%
“…Comparative values also occur for fish in different stages of maturity ( By calculating K identically to that described here, Boothby and Avault (1971) calculated for adult fish in "good condition" as K = 1.3 (1.2-1.6) in winter, 1.4 (1 -2-1.6) in spring, 1.4 (1.2-1.6) in su"er,and 1.5 (1.2-1.7) Log W = -4.7358 + 3.0053 (Log SL).…”
mentioning
confidence: 98%
“…Shrimps and crabs comprised the most frequently encounted crustaceans, and the frequencies of those organisms varied considerably. Gunter (1945) implied that crabs were eaten more in bay waters, whereas shrimp dominated the diet in and near Gulf water; Pearson (1 929) considered the blue crab most important as food when small or in molting condition; Miles (1950) thought fishes and crabs became important when shrimp became scarce; Yokel (1966) found shrimp most important in South Florida from July to September, but crabs most important during the other periods; Yokel also found the red drum to eat proportionally more crabs as it grew larger, with xanthid crabs gaining in importance and portunids losing in importance; and Boothby and Avault (1971) considered crabs and shrimp of equal importance in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Boothby and Avault (1971) found fish in 75% of the Ftomachs constituting 35% of the food's volume in a southeastern Louisiana marsh. All other studies found fish of less importance to drum except that of Inglis (1959) who examined small drum and possibly Breuer (1957) and Simmons (1957) who did not provide data.…”
Section: Discussionmentioning
confidence: 99%